Aspek Reproduksi Ikan Kapiek (Puntius schwanefeldi Bleeker ) di Sungai Rangau â Riau, Sumatra - Yustina Yustina; Arnentis Arnentis (Jurnal Matematika & Sains, 2002)
A study on the reproduction aspect of Kapiek fish (Puntius schwanefeldi Bleeker) at three stations of the Rangau river in Riau â Sumatra was conducted in May â September 2000, by using a cast net and a gill net during trapping periods lasting three nights a month at each station for four months. A total of 375 individuals have been caught. The sexual ratio between males and females was not significantly different from 1. The first gonad maturation is at body weight of 115 g. The body length and body weight are proportional to the gonad maturation degree. The higher the gonad maturation index level, the higher the fecundity. Eggs which are ready to spawn are of diametre 0,27 to 0,40 mm. The distribution of egg diametre indicates that â Kapiekâ belongs to a kind of fish with a large fecundity and using a partial spawning type.